2016
DOI: 10.1103/physrevd.93.064039
|View full text |Cite
|
Sign up to set email alerts
|

Topological black holes in pure Gauss-Bonnet gravity and phase transitions

Abstract: We study charged, static, topological black holes in pure Gauss-Bonnet gravity in asymptotically AdS space. As in general relativity, the theory possesses a unique nondegenerate AdS vacuum. It also admits charged black hole solutions which asymptotically behave as the Reissner-Nordström AdS black hole. We discuss black hole thermodynamics of these black holes. Then we study phase transitions in a dual quantum field theory in four dimensions, with the Stückelberg scalar field as an order parameter. We find in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 84 publications
(114 reference statements)
0
21
0
Order By: Relevance
“…Note from Eqs. (30) and (38) that the module of one trajectory corresponds to the complementary module of the other,…”
Section: Unbounded Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note from Eqs. (30) and (38) that the module of one trajectory corresponds to the complementary module of the other,…”
Section: Unbounded Motionmentioning
confidence: 99%
“…Other studies associated with topological black holes can be found, for example, in Refs. [29,30], among others. Then we obtain the conserved quantities together with the equations of motion for massless particles on these manifolds.…”
Section: Introduction: Conformal Weyl Gravity and Null Geodesicsmentioning
confidence: 99%
“…As was pointed out in Ref. [15], the (A)dS space in the PL theory is not directly related to the sign of a cosmological constant like in General Relativity. Indeed, the definition of (A)dS space is due to the sign of curvature R ab = ∓ 1 ℓ 2 e a e b , and not of the explicit Λ, which now has the dimension of the length −2p (at the same time the dimension of the gravitational constant κ is length 2p−D ).…”
Section: Introductionmentioning
confidence: 81%
“…In the present section we will show how the five-dimensional maximal Pure Lovelock action (the first non trivial example referred also as the Pure Gauss-Bonnet [15,3]) could be obtained from a CS gravity theory for a particular choice of the C m algebra.…”
Section: M Algebras and S-expansionmentioning
confidence: 99%
“…Those symmetries were introduced in Refs.c [28,29,30,31,32,33,34] and can be regarded as generalizations of the so called Maxwell algebra [35,36], which describes the symmetries of quantum fields in Minkowski space with the presence of a constant electromagnetic field. Thus, for completeness and also due to the growing interest in the effect of higher-curvature terms in the holographic context (see for example [37,38,39,40]), in this work we will show that different Lovelock gravity actions in even dimensions can be obtained from a BI action based on the C m algebra. We shall start by considering the six-dimensional spacetime since it allows us to obtain a bigger variety of gravity theories.…”
Section: Introductionmentioning
confidence: 84%